Esquisse d'une évaluation délibérative et apprenante pour penser autrement l'alternance en formation - Lucie Roger; Philippe Maubant (Centre National d'Enseignement à Distance, 2018)
The ambition of alternation as an organizational and pedagogical configuration is closely linked to the question of time. However, no alternation model, no didactic-pedagogical configuration expressing the alternation project, seems to be unanimous among the actors involved in this engineering, whether they are trainers, training managers, "alternates", company tutors. Therefore, to have an expanded view on the possibilities for alternation it seems necessary to questioning the meaning of the temporality and the spaces, by soliciting the situation concept and considering the contribution of the digital resources to elaborate a formation that can create the conditions for professional learning. The dual issue of temporality and spaces of alternating training is considering through the paradigm of learning by exploiting the evaluative moments constitutive of a professionalization process. This paper is a draft of deliberative and learning assessment. It is also revealed another approach to training alternation considering the contribution of digital resources.